OPTIMIZING THE FUNCTIONS OF EDUCATIONAL ADMINISTRATION IN IMPROVING THE EFFECTIVENESS OF THE SCHOOL LEARNING PROCESS - Sinto, Saiful; Kelubas, Rahman; Leunufna, Marthen Jacob; Payapo, Maryam; Hardian, Dafyar Eliadi (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze the role and strategies for optimizing educational administration functions in improving the effectiveness of the learning process in schools. The research method used is descriptive qualitative, with data collection techniques through interviews, observations, and documentation of school principals, administrative staff, teachers, and students. The results show that educational administration plays a crucial role in supporting order, discipline, and learning efficiency. The main obstacles identified include minimal use of technology, limited administrative staff, and a lack of understanding of the strategic role of administration. Suggested optimization strategies include digitizing the administrative system, training administrative staff and teachers, and strengthening coordination between school stakeholders. This study concludes that optimal educational administration functions not only as administrative record-keeping but also as a strategic instrument in improving the quality of learning in schools.